(untitled) (Journal of Hama University, 2025)
In light of the rapid development witnessed by the world at all levels, it is necessary to search for clear foundations for the comprehensive and integrated development of human resources so that they can keep pace with this development, based on the principles of comprehensive quality, which prompted the researcher to choose this research. This research included a number of Arab and foreign studies in this field in addition to the results reached by these studies. The descriptive analytical approach was followed in this research due to its suitability to the nature of the current research and its objectives. The researcher used the content analysis form to determine the degree of availability of Malcolm Baldrige’s principles of comprehensive quality in the content of university admission system plans. The results of the research showed that the degree of availability of Malcolm Baldrige’s principles of total quality in the content of university admission system plans was relatively variable, as the leadership principle came at a rate of 34.3%, followed by the strategic planning principle at a rate of 28.99, and the rest of the principles were less than 16%. The research suggested the importance of developing university admission system plans according to Malcolm Baldrige’s principles of quality in line with global developments.